Struktur Modal pada UMKM Tahu di Kelurahan Tinalan Gang IV Kota Kediri dan Menurut Perspektif Islam - Khabibah, Siti Maria Ulfa; Purnamasari, Puji Endah (Jurnal Manajemen, 2020)
The development of MSMEs (Small, Micro and Medium Enterprises) has several problems, one of them is the capital problem. Lack of capital affected the development rate of MSMEs. It is because most MSMEs use their own capital, so the capital is not too large. One of the reasons MSMEs use their own capital is because of high loan interest and complicated requirements. The importance of capital in a company, so the company must plan the capital appropriately. The purpose of this study was to determine the capital structure of the tofu MSMEs in Tinalan Kelurahan IV, Kediri. This study also aims to know the reason of the business owners use their own funds or external funds that can help their businesses survive and the perception of MSME owners about the increase in capital will affect on the profits. In addition, the research aims to know the reason of business owners saving their funds at home instead of the bank. The method of this research is qualitative research with descriptive approach. This study uses 9 informants from entrepreneurs that include in categories. Data collection techniques use interview and questionnaire. The results showed that the majority of entrepreneurs prefer to use their own capital rather than from banks/ other partnerships, the majority of MSME owners prefer to save their funds at home and they still had low literacy/knowledge of financial.